Influence of masks on speech perception in people with cochlear implants - Teira, Celia; Pomares Gómez, Irene (Revista de Investigación en Logopedia, 2022)
The use of face masks in the COVID-19 health crisis is rising many questions, one of them being the effect that theypotentially have in language perception in deaf people who use a cochlear implant. To shed some light, an experimental study has beenmade on the discrimination of minimal pairs in Spanish. In this experiment, we studied the presence or absence of face mask, as wellthe possibility to read lip and facial expressions. Results support face masks interfere in perception, especially in people with cochlearimplant, but multimodality does not improve it as we expected.
Keywords: cochlear implant; face mask; COVID-19; visual clues; language perception